ANALISIS DAN DESAIN WEBSITE TRACER STUDY SMKN 1 BULIK KABUPATEN LAMANDAU PROVINSI KALIMANTAN TENGAH - Felicia Sylviana; Enny Dwi Oktaviyani (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2015)
SMKN 1 Bulik Lamandau District , Central Kalimantan Province difficult to trace their alumnibecause they do not have the technique to record the alumni . This can happen because the alumni did notreport their workplace , because the work location away from the school , other reasons because of busywork of alumni . Therefore , SMKN 1 Bulik need to create a website design tracer study in the form of thetracer study website blueprint .The method used in the analysis and design of the website tracer study SMKN 1 Bulik is amodified method ( Software Development Life Cycle ) SDLC , with stages of planning , analysis anddesign . Planning stage consists of data collection phase and investigation system . In the planning phaseobtained data and information needed in research . The next stage is the analysis system consists of auser analysis , technology analysis and analysis of information . While the design phase consists ofdatabase design and interface design .Results of this research is the design of the website tracer study in the form of diagrams such asbusiness process diagrams , use case diagrams, activity diagrams and sequence diagrams , EntityRelationship Diagram ( ERD ) and the user interface .